(NmERTWYE DU[I(B: [(NpO\MA(B] / s (N~ASTX (B5s - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1985)
(NtOM SODERVIT PO\MU gOGOLQ (B"(NmERTWYE DU[I(B", (NW TOM ^ISLE SOHRANIW[IESQ GLAWY SOVVENNOGO gOGOLEM WTOROGO TOMA PO\MY(B.s
rus
Keywords: (NpO\ZIQ(B, (NPO\MYs